Polishing of Black and White CVD Grown Polycrystalline Diamond Coatings - Roy, Snigdha; Balla, Vamsi K.; Mallik, Awadesh K.; Ralchenko, Victor G.; Bolshakov, Andrey P.; Ashkinazi, Eugene E. (Journal of Coating Science and Technology, 2018)
Microwave plasma CVD growth can produce black and white varieties of polycrystalline diamond (PCD), depending on their as-grown purity. These two types of PCDs have been polished by mechanical and chemo-mechanical polishing respectively. It has been observed that initial roughness of 2.21μm for white PCD can be brought down to 175 nm after 70 hours of combined polishing, whereas, 85 hours of combined polishing could bring down the high initial roughness of 11.2μm for black PCD down to 546 nm at the end. Although, the material that was removed during polishing was higher for the black variety of PCD but it had lower polishing rate of 4nm/hr than white PCD (13nm/hr) during chemo-mechanical polishing. Such differential polishing rate was due to harder top polished surface of the black diamond than the white diamond. The nanoindentation study on the polished PCD surfaces revealed that the black PCD has a final nanohardness of 32.58±1 GPa whereas the white variety PCD had a polished surface nanohardness of 28.5±2 GPa. More conversion of diamond surface into harder amorphous sp3 than softer graphite during polishing action may have resulted such slow rate of anisotropic polishing for black diamond than white diamond.